Dampak Tanggung Jawab Sosial Perusahaan, Kondisi Keuangan, Pertumbuhan Usaha, dan Ukuran Perusahaan terhadap Respons Pasar atas Informasi Laba SLR - Novitri Kurniati; Rahyatul Maida; Manullang, Jeni (Journal of Creative Student Research, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure, financial distress, corporate growth, and firm size on the Earnings Response Coefficient (ERC).ERC reflects the extent to which the capital market reacts to earnings information announced by firms and serves as an important indicator of earnings quality. This research employs a quantitative approach using secondary data obtained from companies’ financial statements and annual reports. Multiple linear regression analysis is applied to test the influence of the independent variables on ERC. The result indicate that CSR disclosure has a significant effect on ERC, suggesting that social responsibility practices enhance investor confidence and strengthen market reactions to earnings information. In addition, financial distress, corporate growth, and firm size also play a role in determining the magnitude of ERC, as these factors are closely related to perceived risk and future prospects of the firm. The findings imply that non-financial information, particulary CSR disclosure, should be carefully considered by investors and management in decision-making processes within the capital market.